War-induced soil contamination with heavy metals: results from a test site in Mykolaiv region - BONCHKOVSKYI, Oleksandr; OSTAPENKO, Pavlo; ZHUKOVA, Yaroslava; KRAVCHUK, Іllia; PETRYSHCHENKO, Serhii; LAZARETS, Adelina; HALAHAN, Oleksandr; STEPANENKO, Nazar (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2026)
Background. The war in Ukraine is having a serious impact on the physical, chemical and biological properties of soils. Chemical contamination of soil in combat zones is the most discussed issue, as the detonation of various types of weapons releases a range of pollutants into the soil, among which heavy metals are one of the most toxic. Despite the fact that heavy metals are not the main pollutants, they are most often discussed in the literature. Based on a large number of publications, opposing opinions have been formed regarding the level of heavy metal contamination. Methods. The content of heavy metals within a study site of 2000 m2 (Stepova Dolyna village) was measured by portable Xray fluorescence system. In order to identify the precision of XRF analysis, the heavy metals content (Cd, Zn, Pb, Cu, As) was determined using atomic-absorption spectrometry (ContrA 800 D). Results. A study of the lateral variability of the content of various heavy metals at a test site in Mykolaiv region, which was heavily damaged by artillery shelling in 2022, found virtually no heavy metal contamination in the soil (except for cadmium in one sample). In most cases, the content of the heavy metals is not mostly related to the location of craters, except for lead, which showed increased concentrations near craters. The very good agreement between portable XRF analyser and atomic-absorption spectrometry was found for lead content. Due to low concentrations of copper, cadmium and arsenic in the soil, the XRF analyser could not measure them. Conclusions. At the study site, the soil contamination with heavy metals due to explosion of artillery shells, MLRS and mortar is slight. There is no traceable enrichment with heavy metals near craters that can indicate drawbacks of taking incremental samples in case of high-resolution studies. The use of a portable XRF analyser allows for rapid screening of the war-damaged soils for heavy metals and the identification of heavy metal contamination sites. However, accurate data on heavy metals contamination require more precise laboratory methods.
Keywords: Russia-Ukraine war; soil; heavy metals; contamination; portable X-ray fluorescence system; atomic- absorption spectrometry